PENGEMBANGAN E-MODUL IPA BERBANTUAN FLIPPED CLASSROOM UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP - Siti Damaiyanti; Destien Atmi Arisandy; Yunita Wardianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a valid, practical, and effective e-module based on the flipped classroom model for the material on the human circulatory system. The research method employed is Research and Development (R&D) using the 4D development model (Define, Design, Develop, Disseminate). Research instruments included validity questionnaires, practicality questionnaires, and learning outcome tests. The findings indicate that the e-module is highly valid, with an average score of 4.75 from experts. Practicality reached the "very practical" category, scoring 97.33% from teachers and 98.81% from students. In terms of effectiveness, there was a significant improvement in learning outcomes, evidenced by an N-Gain score of 0,86 (high category) and a 100% student mastery rate. The implication of this research is that the flipped classroom-based e-module serves as an innovative solution for educators to create interactive, independent, and student-centered science learning to enhance the quality of learning outcomes at the junior high school level.